Porphyromonas gingivalis initiates coagulation and secretes polyphosphates — A mechanism for sustaining chronic inflammation?. (January 2022) - Neilands, Jessica; Kinnby, Bertil
Abstract: Background: Periodontitis is a chronic inflammation resulting in destruction of tooth-supporting bone. Chronic inflammation is characterized by extravascular fibrin deposition. Fibrin is central to destruction of bone; monocytes bind to fibrin and form osteoclasts, thus providing a link between coagulation and the tissue destructive processes in periodontitis. The oral microbiome is essential to oral health. However, local ecological changes, such as increased biofilm formation, result in a dysbiotic microbiome characterized by an increase of protease-producing species e.g. Porphyromonas gingivalis. Proteases initiate inflammation and may cleave coagulation factors. Polyphosphates (polyP) may also provide bacteria with procoagulant properties similar to platelet-released polyP. P. gingivalis has also been found in remote locations related to vascular pathology and Alzheimer's disease. Objectives: The aim of this study was to investigate procoagulant activity of ten different species of oral bacteria present in oral health and disease as well as presence of polyP and fibrin formation in planktonic and biofilm bacteria. Methods: Oral bacteria were studied for protease production and procoagulant activity. The presence of polyP and formation of fibrin was observed using confocal microscopy. Results: P. gingivalis showed strong protease activity and was the only species exerting procoagulant activity. Confocal microscopy showed polyP intracellularly in planktonic bacteria and extracellularly after biofilm formation. Fibrin formation emanated from planktonic bacteria and from both bacteria and polyP in biofilm cultures. Conclusions: The procoagulant activity of P. gingivalis could explain its role in chronic inflammation, locally in oral tissues as well as in remote locations. Graphical abstract: Image 1 Highlights: Extravascular fibrin promotes chronic inflammation. Periodontitis is a chronic inflammatory disease. Procoagulant activity of oral bacteria was tested in vitro and polyP studied by confocal microscopy. P.gingivalis initiated coagulation through arginine gingipain and secreted polyP after biofilm formation. Procoagulant activity of P. gingivalis is likely to contribute to sustaining chronic inflammation.